(-3m)(2m)=

Simple and best practice solution for (-3m)(2m)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3m)(2m)= equation:


Simplifying
(-3m)(2m) = 0

Remove parenthesis around (-3m)
-3m(2m) = 0

Remove parenthesis around (2m)
-3m * 2m = 0

Reorder the terms for easier multiplication:
-3 * 2m * m = 0

Multiply -3 * 2
-6m * m = 0

Multiply m * m
-6m2 = 0

Solving
-6m2 = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-6'.
m2 = 0

Simplifying
m2 = 0

Take the square root of each side:
m = {0}

See similar equations:

| f(x+1)=x^2-8x | | 2(2x-4)=6x-1.8 | | 132.49+15=192.49 | | 4-(-5)+16= | | -2x^2+324=0 | | (N+5)(N+3)= | | 4(2p+1)=2p | | 10(38-(7x+5x))+(7x+5x)=176 | | (38-(7x+5x))+(7x+5x)=176 | | 10x^3=1000 | | 10((38-(7x+x))+(7x+x))=176 | | (38-(7x+x))+(7x+x)=38 | | 9t+4=5t+8 | | x+x+46=180 | | x*0.85=16688 | | 6x^3+2x^2+110x-182=0 | | x*0.85=12 | | y^2+10x^2=121 | | 11+7x=95 | | 60=x-10+.20x+10 | | Y=ln*4*x | | (2y-x^3)dx+xdy=0 | | 26/81 | | 26-33/4=-2/3f-1/4 | | 2=3.5n-8 | | x+2/x+14=10/x+10 | | (2-v)/2=(3v-2)/5 | | 1+(2p+1)=2p | | y=-2x+2graph | | (2-v)/2=((3v | | 2n=3.5-8 | | b(b-5)=24 |

Equations solver categories